2022
DOI: 10.1155/2022/3556330
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Clinical Analysis of Surgical Treatment of Senile Intertrochanteric Fracture Based on Intelligent Knowledge of Health Care

Abstract: In order to explore the clinical application value of intelligent health care knowledge combined with closed reduction intramedullary nail fixation in elderly patients with intertrochanteric fracture of the femur, a retrospective analysis is performed on 80 elderly patients who received intertrochanteric surgery from January 2019 to January 2021. All patients were divided into study group and control group based on intelligent medical knowledge received or not. During the phase of treatment, both the two group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Subtrochanteric fractures were defined as fractures occurring within 5 cm distal to the lesser trochanter [ 19 , 20 ]. Pertrochanteric fracture of femur refers to the fracture from the base of femoral neck to the level above the lesser trochanter [ 21 ]. Fracture of neck of femur refer to the fractures occurring between the femoral head and the basal part of the femoral neck [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Subtrochanteric fractures were defined as fractures occurring within 5 cm distal to the lesser trochanter [ 19 , 20 ]. Pertrochanteric fracture of femur refers to the fracture from the base of femoral neck to the level above the lesser trochanter [ 21 ]. Fracture of neck of femur refer to the fractures occurring between the femoral head and the basal part of the femoral neck [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%